2003
DOI: 10.1081/ss-120020126
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Transport of Toluene and Phenol Through Organic Solvent Nanofiltration Membranes

Abstract: Overall mass transfer coefficients (OMTCs) during membrane solvent extraction (MSE) for a microfiltration membrane Accurel, an organic solvent nanofiltration (OSN) membrane MPF 50, and silicone rubber were investigated with a hydrophilic solute (phenol) and a hydrophobic solute (toluene) in a membrane solvent extractor. Decanol was used to extract phenol or toluene from water. In MSE of phenol from water, MPF 50 has an OMTC intermediate between Accurel and silicone rubber, and has a much higher breakthrough pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
(12 reference statements)
0
15
0
Order By: Relevance
“…They concluded that solution-diffusion based models give a better description of permeation through flexible chain glassy membranes and rubbery membranes than pore flow based models. Similarly, Silva et al [8], Han et al [26] and Peeva et al [27] studied the permeation of pure organic solvents and organic solvent/water mixtures through STARMEM™ 122 membranes and concluded that the solution diffusion model gives a better prediction than the pore flow model. In order to describe membrane transport in the presence of highly concentrated solutions, Silva et al [8] and Peeva et al [27] considered the thermodynamic non-ideality of the solution and the occurrence of concentration polarisation, by introducing activity coefficients and the film theory into the classical solution diffusion model.…”
Section: Membrane Transport Model and Regression Of The Permeability mentioning
confidence: 96%
“…They concluded that solution-diffusion based models give a better description of permeation through flexible chain glassy membranes and rubbery membranes than pore flow based models. Similarly, Silva et al [8], Han et al [26] and Peeva et al [27] studied the permeation of pure organic solvents and organic solvent/water mixtures through STARMEM™ 122 membranes and concluded that the solution diffusion model gives a better prediction than the pore flow model. In order to describe membrane transport in the presence of highly concentrated solutions, Silva et al [8] and Peeva et al [27] considered the thermodynamic non-ideality of the solution and the occurrence of concentration polarisation, by introducing activity coefficients and the film theory into the classical solution diffusion model.…”
Section: Membrane Transport Model and Regression Of The Permeability mentioning
confidence: 96%
“…In microporous MBBs, the breakthrough pressure is dramatically decreased by the presence of surfactants in the biomedium which reduces the surface tension between the two liquid phases [4][5][6]11,12]. Han et al reported a 30 bar breakthrough pressure in MPF 50, an OSN composite membrane [34], which is very much above the maximum pressure attainable in our system (0.4 bar). Considering the surfactantadsorption mechanism for the reduction of the breakthrough pressure outlined by Shroen et al [12] and Vaidya et al [11], a decrease in this pressure due to the presence of surfactants in the biomedium, such as enzymes, seems unlikely to occur in the OSN-MBB because the nano-scale of the membrane pores prevents adsorption of surfactants into the pore walls.…”
Section: Comparison To Other Membrane Bioreactorsmentioning
confidence: 85%
“…2 [34]. The membrane, with an effective area of 0.015 m 2 , was placed in the middle of two stainless-steel half-cells with the active layer facing the aqueous phase.…”
Section: Mass Transfer Experiments and Mbbmentioning
confidence: 99%
“…Yang et al (2001) showed that viscous flow could not describe their measurements. Han et al (2003) used the MPF50 membrane in a solvent membrane extractor and suggested that solution-diffusion type models may be more appropriate than pore-flow models for describing transport of solvents through SRNF membranes. Machado et al (1999) measured the effect of temperature on the acetone flux through MPF-50 and MPF-60 membranes.…”
Section: Introductionmentioning
confidence: 99%